Predictors of patient survival following liver transplant in non-alcoholic steatohepatitis: A systematic review and meta-analysis. (August 2022) - Minich, Adam; Arisar, Fakhar Ali Qazi; Shaikh, Noor-ul Saba; Herman, Leanne; Azhie, Amirhossein; Orchanian-Cheff, Ani; Patel, Keyur; Keshavarzi, Sareh; Bhat, Mamatha
Summary: Background: Non-alcoholic steatohepatitis (NASH) is the second-leading indication for liver transplantation (LT) worldwide and is projected to become the leading indication. Our study aimed to determine clinical variables that predict post-LT survival in NASH. Methods: A systematic review and meta-analysis was performed. On June 18, 2020 and April 28, 2022, Ovid MEDLINE ALL, Ovid Embase, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials were searched. No date limits were applied. Inclusion criteria specified the type of study and our study's population/comparison and outcome/timepoints. Pediatric, animal, retransplantation-only, and studies classifying cryptogenic cirrhosis patients with body mass index (BMI) <30 as NASH were excluded. Studies with duplicate cohorts and missing information were excluded from the meta-analysis. Studies were appraised using the Newcastle–Ottawa Scale. This study was preregistered in PROSPERO (CRD42020196915). Findings: Out of 8583 studies identified, 25 studies were included in the systematic review, while 5 studies were included in the meta-analysis. Our quantitative review suggested that the following variables were predictive of post-LT NASH patient survival: recipient age, functional status, pre-LT hepatoma, model for end-stage liver disease (MELD) score, diabetes mellitus (DM), pre-LT dialysis, hepatic encephalopathy, portal vein thrombosis, hospitalization/ICU at LT, and year of LT. Predictors of graft survival included recipient age, BMI, pre-LT dialysis, and DM. Our pooled meta-analyses included five predictors of patient survival. Increased patient mortality was associated with older recipient age (HR=2·07, 95%CI: 1·71-2·50, I 2 =0, τ 2 =0, p =0·40) and pretransplant DM (HR=1·18, 95%CI: 1·08-1·28, I 2 =0, τ 2 =0, p =0·76). Interpretation: Our systematic review and meta-analysis aimed to synthesise predictive variables of mortality in LT NASH patients. Clinically, this might help to identify modifiable risk factors that can be optimized in the post-transplant setting to improve patient outcomes and optimises decision making in the resource-limited LT setting. Funding: Toronto General and Western Hospital Foundation.